Reclaiming the Empirical: Artificial Intelligence and Literary Genres (Comparatismi, 2025)
The paper explores the relationship between AI and literary genres, highlighting their shared features. Both occupy a borderline space between creativity and interpretation, the author’s intentionality and the critic’s gaze. Another convergence is the tension between imposed rules and emerging patterns, which reflects the distinction between a normative and a descriptive conception. The study reviews several applied studies that employ AI for text classification, to bring out tendencies such as emotional dimension, cultural diversity, character networks, and paratextual aspects. Building on this body of work, it develops a theoretical reflection on how AI systems can contribute to redefining the category of literary genre. What emerges is a view of genre as an empirical and pragmatic construct, culturally situated and historically differentiated, composed of heterogeneous elements.
Keywords: Artificial Intelligence; Genre; Empirical; Theory